2022
DOI: 10.1021/acs.joc.2c00498
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Alkynylation of Enones with Alkynylsilanes via C–C Bond Activation

Abstract: We report herein the synthesis of 1,3-enynes via palladium-catalyzed cross-coupling between enone derivatives and alkynylsilanes. The employment of an appropriate pyridine-oxazoline ligand is the key to the C−C cleavage and the high E/Z stereoselectivity. This protocol features broad substrate scope and wide functional-group tolerance, affording the desired products in moderate-to-good yields. Late-stage diversification of natural product β-ionone further demonstrated the synthetic utility of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Encouraged by our previous arylation, alkenylation, alkylation, borylation, and silylation of aryl ketone, [ 57‐68 ] we next began to explore these protocols to synthesize the syringin analogues (Scheme 4). Aryl boron reagents bearing ‐t ‐Bu, ‐Me and ‐OMe gave the desired products 4a—4c in moderate yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by our previous arylation, alkenylation, alkylation, borylation, and silylation of aryl ketone, [ 57‐68 ] we next began to explore these protocols to synthesize the syringin analogues (Scheme 4). Aryl boron reagents bearing ‐t ‐Bu, ‐Me and ‐OMe gave the desired products 4a—4c in moderate yields.…”
Section: Resultsmentioning
confidence: 99%
“…[ 55‐56 ] Recently, our group reported the palladium‐catalyzed ligand‐promoted C(O)–C bond cleavage of unstrained aryl ketones (Scheme 1b). [ 57‐68 ] Considering the broad biological activites of syringin, herein, we present our achievement in the total synthesis of syringin, in which palladium‐catalyzed C(O)–C bond functionalization of cheap acetosyringone supported the key transformations (Scheme 1c). Furthermore, various syringin analogues bearing alkynyl, alkenyl, aryl, alkyl, siliconyl, and boronyl groups were also constructed via the aryl palladium intermediate.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Olefinic C­(sp 2 )–H alkynylation has been an active area of research in the past decade for the flexibility of introducing complex groups and constructing novel compounds. In the past decades, much progress has been achieved in the direct olefinic C­(sp 2 )–H alkynylation using noble transition metals such as Pd, Rh, Ru, and Au, and the participation of chelation-assisted systems with N , N -bidentate directing groups has been an ideal approach to achieve site-selective C–H bond functionalization. Recently, the development of direct C–H alkynylation catalyzed by 3d transition metals to construct C­(sp 2 )–C­(sp) bonds has been a promising direction because of their low price and lower toxicity. For instance, in 2015, Yi et al reported a nickel-catalyzed C–H alkynylation reaction between two kinds of inactivated C­(sp 2 )–H and triisopropylsilyl (TIPS)-substituted bromoalkyne, which is the first report on Ni-catalyzed C­(sp 2 )–C­(sp) bond formation via 8-quinolinyl-chelation assistance .…”
Section: Introductionmentioning
confidence: 99%
“…General methods for the synthesis of conjugated 1,4-diarylenynes, where the substituents in the 1-and 4-positions are different. The available procedures include cross-coupling reactions, (i.e., Suzuki [17], Stille [18], Hiyama-Denmark [19], Sonogashira [20][21][22][23][24], Heck [25]) (A), Kumada [26], and Suzuki [27] (B), the hydroarylation of 1,3-diynes [28,29] (C), the hydroalkynylation of alkynes and/or allenes (D) [30,31], and a few less general procedures [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%